Characterization of the Hamamatsu VUV4 MPPCs for nEXO - Gallina, G.; Giampa, P.; Retière, F.; Kroeger, J.; Zhang, G.; Ward, M.; Margetak, P.; Li, G.; Tsang, T.; Doria, L.; Al Kharusi, S.; Alfaris, M.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
In this paper we report on the characterization of the Hamamatsu VUV4 (S/N: S13370-6152) Vacuum Ultra-Violet (VUV) sensitive Multi-Pixel Photon Counters (MPPC)s as part of the development of a solution for the detection of liquid xenon scintillation light for the nEXO experiment. Various MPPC features, such as: dark noise, gain, correlated avalanches, direct crosstalk and Photon Detection Efficiency (PDE) were measured in a dedicated setup at TRIUMF. MPPCs were characterized in the range 163K≤T≤233K. At an over voltage of 3.1±0.2 V and at T=163K we report a number of Correlated Avalanches (CAs) per pulse in the 1μs interval following the trigger pulse of 0.161±0.005. At the same settings the Dark-Noise (DN) rate is 0.137±0.002Hz/mm2. Both the number of CAs and the DN rate are within nEXO specifications. The PDE of the Hamamatsu VUV4 was measured for two different devices at T=233K for a mean wavelength of 189±7nm. At 3.6±0.2 V and 3.5±0.2 V of over voltage we report a PDE of 13.4±2.6% and 11±2%, corresponding to a saturation PDE of 14.8±2.8% and 12.2±2.3%, respectively. Both values are well below the 24% saturation PDE advertised by Hamamatsu. More generally, the second device tested at 3.5±0.2 V of over voltage is below the nEXO PDE requirement. The first one instead yields a PDE that is marginally close to meeting the nEXO specifications. This suggests that with modest improvements the Hamamatsu VUV4 MPPCs could be considered as an alternative to the FBK-LF Silicon Photo-Multipliers for the final design of the nEXO detector.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Hamamatsu; MPPCs; nEXO; PDE; SiPMs; VUV4